The effect of inventory leanness on firms’ credit ratings: The case of Pakistan - Carvalho, P. V.; Shah, S. S. H.; Zaheer, A.; Mata, M. N.; Lourenço, A. M. (Risks, 2022)
Inventory leanness requires that firms minimize inventory mistreatment and misuse. A firm performance deteriorates because of high inventory misuse, and because of such an issue, the effect on the firm’s credit rating can also be seen. This study examines the effect of inventory leanness on firms’ credit ratings. It aims to create an understanding of the relationship between inventory leanness and the firm’s financial performance and provides insight into the credit rating system of Pakistan. We analyze secondary Pakistan data between 2008 and 2017. Among the sixty firms on Pakistan Stock Exchange that are rated by PACRA, only thirty-eight have complete data available on their respective websites. By using panel data analysis, the results indicate that inventory leanness and credit ratings are positively related. In an added analysis, we evaluate the financial performance in the context of credit rating by using control variables (size, leverage, and capital intensity ratio) and dummy variables (loss and subordinate debt). Our results are consistent with earlier studies.